2012
DOI: 10.1128/ec.00095-12
|View full text |Cite
|
Sign up to set email alerts
|

The Tlo Proteins Are Stoichiometric Components of Candida albicans Mediator Anchored via the Med3 Subunit

Abstract: ABSTRACTThe amplification of theTLO(fortelomere-associated) genes inCandida albicans, compared to its less pathogenic, close relativeCandida dubliniensis, suggests a role in virulence. Little, however, is known about the function of the Tlo proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(118 citation statements)
references
References 51 publications
2
114
0
Order By: Relevance
“…The absence of Med8 from the large-scale data set is not surprising, since the tryptic peptide generated form the N terminus of Med8, which contains the most likely Cdk8 P sites, is above the molecular mass typically detected by this methodology. To determine if Cdk8 can phosphorylate a Tlo protein family member and Med3, we performed an [ 32 P]ATP kinase assay in which purified Mediator was incubated with a complex of recombinant Tlo␣12 bound to 6ϫHis-tagged Med3 (44). The phosphorylation pattern showed that the recombinant proteins were detected in a dose-dependent manner at the expected sizes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of Med8 from the large-scale data set is not surprising, since the tryptic peptide generated form the N terminus of Med8, which contains the most likely Cdk8 P sites, is above the molecular mass typically detected by this methodology. To determine if Cdk8 can phosphorylate a Tlo protein family member and Med3, we performed an [ 32 P]ATP kinase assay in which purified Mediator was incubated with a complex of recombinant Tlo␣12 bound to 6ϫHis-tagged Med3 (44). The phosphorylation pattern showed that the recombinant proteins were detected in a dose-dependent manner at the expected sizes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Mediator complex was purified from the high-salt elution fraction of the heparin column by Flag affinity purification through the 6ϫHis-3ϫFlag tag placed on the C terminus of the Med8 (cTTR03) or Ssn3 (yLM256) subunit as previously described (44). Free CDK8 module, containing only Ssn3/Cdk8, Ssn8/CycC, Ssn5/Med12, and Ssn2/Med13, was purified from the heparin flowthrough fraction of yLM255 lysate by Flag purification.…”
Section: Go Term Analysismentioning
confidence: 99%
“…Most strains, except where noted, were derived from the SN152 (53) MTLa/a strain. The specific open reading frames (ORFs) of Mediator subunit genes were previously identified (13). Mediator subunit single gene deletions (med5⌬/ ⌬, med9⌬/⌬, med1⌬/⌬, med16⌬/⌬, med3⌬/⌬, med15⌬/⌬, med20⌬/⌬, med12⌬/⌬) were created by using the C. maltosa LEU2 and C. dubliniensis HIS1 fusion PCR cassettes as described by Noble and Johnson (53).…”
Section: Methodsmentioning
confidence: 99%
“…Saccharomyces cerevisiae Mediator (scMediator) has structurally distinct modules referred to as Tail, Middle, Head, and Cdk8 (9)(10)(11)(12). Purification and characterization of Candida albicans Mediator (caMediator) (13) showed that the caMediator complex has a composition and architecture similar to that of scMediator. Certain scMediator subunits are critical for the activation of specific sets of genes (14,15), and the Tail module has been shown to be a direct target of activation domains (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…We found that the C. albicans TLO gene family is continuing to rapidly evolve, including changes both in the number and relative positions of TLO genes within the genome. TLO genes encode proteins with similarity to Med2, a component of Mediator that regulates transcription by RNA polymerase II; and some Tlo proteins have been confirmed as Med2-like Mediator components (Zhang et al 2012). TLO gene expression is also highly variable due primarily to Sir2-dependent telomere associated silencing (Anderson et al 2014).…”
Section: Intra-species Variation In Candida Albicansmentioning
confidence: 99%